Preclinical In Silico Evidence Indicates the Pharmacological Targets and Mechanisms of Mogroside V in Patients With Ovarian Cancer and Coronavirus Disease 2019 - Li, Yongming; Chen, Yudong; Wei, Mulan; Wei, Chaohe (Frontiers in Endocrinology, 2022)
The borderless transmission of coronavirus remains uncontrolled globally. The uncharted severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variant reduces the therapeutic efficacy of vaccines against coronavirus disease 2019 (COVID-19). Clinical observations suggest that tumour cases are highly infected with coronavirus, possibly due to immunologic injury, causing a higher COVID-19-related death toll. Presently, screening of candidate medication against coronavirus is in progress. Mogroside V, a bioactive ingredient of Siraitia grosvnorii, has been reported in China to have lung-protective and anticancer effects. The current study used network pharmacology and molecular docking to unlock the potential drug targets and remedial mechanisms of mogroside V against patients with ovarian cancer with COVID-19 . We identified 24 related targets of mogroside V in patients with ovarian cancer and COVID-19, and characterised another 10 core targets of mogroside V against COVID-19 ovarian cancer, including Jun, IL2, HSP90AA1, AR, PRKCB, VEGFA, TLR9, TLR7, STAT3, and PRKCA. The core targets' biological processes and signalling pathways were revealed by enrichment analysis. Molecular docking suggested favourable docking between core target protein and mogroside V, including vascular endothelial growth factor A (VEGFA). These findings indicated that mogroside V might be a potential therapeutic agent in the mitigation of COVID-19 ovarian cancer.